2007
DOI: 10.2217/17460913.2.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Immunosuppressive Properties of Bacterial Prodiginines

Abstract: Bacterial prodiginines are a family of red-pigmented, tripyrrolic compounds that display numerous biological activities, including antibacterial, antifungal, antiprotozoal, antimalarial, immunosuppressive and anticancer properties. Recently, significant progress has been made in understanding the biosynthesis and regulation of bacterial prodiginines. An understanding of the biosynthesis of prodiginines will allow engineering of bacterial strains capable of synthesizing novel prodiginines through rational desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
118
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(124 citation statements)
references
References 106 publications
0
118
0
3
Order By: Relevance
“…In this regard, a diverse group of anionophores, lipid soluble compounds that facilitate the transport of anions across cell membranes, have recently emerged as promising anticancer compounds [8,9]. Indeed, prodigiosin, a tripyrrolic natural product with anticancer properties, represents one of the first described anionophores [10][11][12][13]. It has been reported that its biological activity is partly due to its ability to deacidify acidic compartments within cells, which may cause a drop in pHi, and therefore the onset of apoptosis in cancer cells [9,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a diverse group of anionophores, lipid soluble compounds that facilitate the transport of anions across cell membranes, have recently emerged as promising anticancer compounds [8,9]. Indeed, prodigiosin, a tripyrrolic natural product with anticancer properties, represents one of the first described anionophores [10][11][12][13]. It has been reported that its biological activity is partly due to its ability to deacidify acidic compartments within cells, which may cause a drop in pHi, and therefore the onset of apoptosis in cancer cells [9,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Prodigiosin, a red pigment produced by bacteria as a bioactive secondary metabolite, displays numerous biological activities, including antibacterial, antifungal, antiprotozoal, antimalarial, immunosuppressive, and anticancer properties (8)(9)(10)(11)(12)(13). The prodigiosin analog obatoclax is currently in clinical trials in patients with cancer (14,15).…”
mentioning
confidence: 99%
“…The prodigiosin analog obatoclax is currently in clinical trials in patients with cancer (14,15). Prodigiosin has exhibited potent cytotoxic activity against human cancer cell lines with multidrug resistance phenotypes or defects in apoptotic pathways, with much less toxicity to normal cells (12,13,16). The specific mechanisms of prodigiosin action in malignant cells have been poorly elucidated, however.…”
mentioning
confidence: 99%
“…19,20 This tripyrrolic metabolite has been found to have potent inmunosuppresive and anticancer activities. Prodigiosin appears to cause apoptosis of cancer cells selectively, 21 and the structural analogue obatoclax is currently in clinical trials for the treatment of cancer. 22 The origin of the biological activity has yet to be unambiguously established, although there is evidence that this class of compound facilitates the co-transport of HCl [23][24][25][26][27][28] and/or the anion exchange of chloride 29,30 across lipid bilayer membranes.…”
mentioning
confidence: 99%